2015
DOI: 10.1111/pan.12749
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pain at home and its consequences in children following two types of short stay surgery: a multicenter observational cohort study

Abstract: The prevalence of pain at home, and its potential associated consequences, is high following short stay surgery in children in the UK. In both groups, high incidences were seen for longer periods than is commonly perceived. These findings were consistent between the centers involved suggesting that this is a significant national healthcare issue with potential short- and long-term consequences for the child, their family, and health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
1
22
1
2
Order By: Relevance
“…In that study, however, less children overall experienced pain on the day of surgery (68% vs 86% in this study) or on the first postoperative day (43% vs 65% in our study) . In patients undergoing orchidopexy, other studies either reported similar pain scores on the day of surgery and first postoperative day (72% in pain on day of surgery and 74% on the first postoperative day, compared with 72% and 62%, respectively, in our study), and higher pain scores on the second postoperative day (70% in pain on the second postoperative day vs 47% in our study) . Pain after umbilical hernia repair is poorly studied, with only 3 patients with 48‐hour follow‐up previously described, and reported together with other surgical conditions limiting interpretation .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In that study, however, less children overall experienced pain on the day of surgery (68% vs 86% in this study) or on the first postoperative day (43% vs 65% in our study) . In patients undergoing orchidopexy, other studies either reported similar pain scores on the day of surgery and first postoperative day (72% in pain on day of surgery and 74% on the first postoperative day, compared with 72% and 62%, respectively, in our study), and higher pain scores on the second postoperative day (70% in pain on the second postoperative day vs 47% in our study) . Pain after umbilical hernia repair is poorly studied, with only 3 patients with 48‐hour follow‐up previously described, and reported together with other surgical conditions limiting interpretation .…”
Section: Discussionsupporting
confidence: 64%
“…24 In patients undergoing orchidopexy, other studies either reported similar pain scores on the day of and 74% on the first postoperative day, compared with 72% and 62%, respectively, in our study), 25 and higher pain scores on the second postoperative day (70% in pain on the second postoperative day vs 47% in our study). 26 Pain after umbilical hernia repair is poorly studied, with only 3 patients with 48-hour follow-up previously described, and reported together with other surgical conditions limiting interpretation. 7 Pain severity and prevalence was high for this procedure (67% had moderate or severe pain on the day of surgery), and requires improved management.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly controlled oropharyngeal pain may lead to decreased oral intake, dysphagia, and dehydration and has been cited as one of the leading causes of the need for hospital readmission. [2][3][4] For the medical team caring for the OSA or SDB patient presenting for tonsillectomy, the control of postoperative pain can be challenging. A balance must be struck between the analgesic needs of the patient and the understanding that OSA patients exhibit an increased sensitivity to opioids and are at risk for postoperative respiratory complications, morbidity, and even mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In the past we happily sent children home from hospital with codeine following certain types of surgery. Many institutions are now limiting the use of morphine as take-home medication despite the evidence that many children experience considerable pain following surgery 15. In my view the risks from morphine are minimal provided there is appropriate guidance available both for healthcare professionals and carers alongside regular audit and review of practice, the only caveat being children with obstructive sleep apnoea or sleep disordered breathing in whom morphine should be avoided due to a greater susceptibility to respiratory depression 16.…”
Section: Oral Morphinementioning
confidence: 99%